2021
DOI: 10.1111/jmft.12474
|View full text |Cite
|
Sign up to set email alerts
|

“The troublesome other and I”: Parallel stories of separated parents in prolonged conflicts

Abstract: This qualitative study aims to explore how noncohabiting parenting couples in prolonged conflict construct the other parent and themselves. Ten parents from five parent couples were interviewed. A dyadic analytical design was used, where parent's stories of conflict were analyzed in parallel with their co‐parent. Drawing on positioning theory, self‐identity as parents emerged as implicit counter positions in storylines, which construct the co‐parent as “the troublesome other.” Two typologies of conflicted stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…By founding our research on the causality pillar and thereby, by extension, assessing for the assumed interdependence of observations (i.e., a test of nonindependence in quantitative methodology; Kenny et al, 2020), we are in a position to empirically test hypotheses generated by family systems theory (Priest, 2021) relating to how systems change across time. Similarly, one could supplement quantitative tests of non-independence with indepth interviews to method triangulate (Fielding, 2012) and hence explore links between statistical associations (e.g., actor and partner effects; Kenny et al, 2020) and meaning-making from different subject positions on relational processes (e.g., self/another positioning, positioning theory; Stokkebekk, 2022;Stokkebekk et al, 2019Stokkebekk et al, , 2021Stokkebekk et al, , 2022.…”
Section: T H E F I V E Pi L L a R Smentioning
confidence: 99%
“…By founding our research on the causality pillar and thereby, by extension, assessing for the assumed interdependence of observations (i.e., a test of nonindependence in quantitative methodology; Kenny et al, 2020), we are in a position to empirically test hypotheses generated by family systems theory (Priest, 2021) relating to how systems change across time. Similarly, one could supplement quantitative tests of non-independence with indepth interviews to method triangulate (Fielding, 2012) and hence explore links between statistical associations (e.g., actor and partner effects; Kenny et al, 2020) and meaning-making from different subject positions on relational processes (e.g., self/another positioning, positioning theory; Stokkebekk, 2022;Stokkebekk et al, 2019Stokkebekk et al, , 2021Stokkebekk et al, , 2022.…”
Section: T H E F I V E Pi L L a R Smentioning
confidence: 99%
“…The research literature (Anderson et al., 2010; Haddad, Phillips, & Bone, 2016; Johnston, 1994; Kosher & Katz, 2022; Smyth & Moloney, 2019; Stokkebekk, Iversen, Hollekim, & Ness, 2021) shows great variation in terminology when describing parental conflict. Coleman (2014) labels prolonged marital disputes as intractable conflicts characterised by escalation, hostile interactions, sentiment, and a change in quality over time.…”
Section: Theoretical Perspective: Tame and Wicked Problemsmentioning
confidence: 99%
“…Recent research identified two common typologies of conflicted storylines. Storylines of violations of trust, positioning the co‐parents in relation to traumatic events in the past, and storylines of who is bad, positioning the co‐parent as either a disloyal co‐parent or a dysfunctional parent (Stokkebekk et al, 2020). The overarching conclusion is that cooperation and reconciliation of positions seems to be unreachable, unless the meaning framework of reference is changed.…”
Section: Introductionmentioning
confidence: 99%